Lung metastasectomy for osteosarcoma in children, adolescents, and young adults: proof of permanent cure. Issue 1 (February 2023) - Pastorino, Ugo; Palmerini, Emanuela; Porcu, Luca; Luksch, Roberto; Scanagatta, Paolo; Meazza, Cristina; Leuzzi, Giovanni; Massimino, Maura; Picci, Piero
Introduction: Surgical resection of pulmonary metastases has been associated with increased survival at 5 years for osteosarcoma, but limited information is available on long-term outcome, role of repeated metastasectomies, and surgical sequelae in a pediatric population. We analyzed a consecutive series of children, adolescents, and young adults (AYA) treated by repeated lung metastasectomies during a period >40 years to estimate the clinical benefit and potential cure rate of salvage surgery. Methods: All patients who underwent lung metastasectomy for osteosarcoma at the IRCCS Istituto Ortopedico Rizzoli of Bologna, University of Modena, and IRCCS Istituto Nazionale Tumori of Milan from May 1973 to January 2014 were included. Overall survival (OS) at 20 years from the first metastasectomy was calculated. Results: A total of 463 consecutive children and AYA were analyzed. Median age was 15.9 years (range 0.2–23.2 years) and median follow-up 18.6 years. The 5- and 20-year OS were 34.0% and 29.7% (95% CI 25.5–34.0%). Among the 138 (29.8%) alive patients, 42 (30.4%) had disease recurrence cured by repeated metastasectomies. Disease-free interval from primary tumor, number of metastases, and complete resection were the most relevant survival predictors at multivariable model analysis. Discussion: The extended follow-up of this consecutive series shows that repeated lung metastasectomy can achieve a permanent cure when offered to properly selected patients with metastases from osteosarcoma.